A process for assessing and prioritizing species conservation needs: going beyond the Red List. Issue 1 (26th June 2018) - Johnson, Kevin; Baker, Anne; Buley, Kevin; Carrillo, Luis; Gibson, Richard; Gillespie, Graeme R.; Lacy, Robert C.; Zippel, Kevin
Abstract: Conservation resources are limited, yet an increasing number of species are under threat. Assessing species for their conservation needs is, therefore, a vital first step in identifying and prioritizing species for both ex situ and in situ conservation actions. Using a transparent, logical and objective method, the Conservation Needs Assessment process developed by Amphibian Ark uses current knowledge of species in the wild to determine those with the most pressing conservation needs, and provides a foundation for the development of holistic conservation action plans that combine in situ and ex situ actions as appropriate. These assessments allow us to maximize the impact of limited conservation resources by identifying which measures could best serve those species requiring help. The Conservation Needs Assessment complements the IUCN Red List assessment, and together they provide a more holistic guide to conservation priorities and actions. Conservation Needs Assessments generate national prioritized lists of species recommended for conservation action. These can subsequently be used to assist in the development of species recovery plans and national action plans, or to inform national conservation priorities better. Additional tools that will evaluate the recommendations for ex situ rescues, to determine the best candidates for conservation breeding programmes, are currently under development.